Emergency department presentations related to asthma and allergic diseases in Central Queensland, Australia: a comparative analysis between First Nations Australians and Australians of other descents - Peter D Sly; Rachel L Peters; Jennifer J Koplin; Gulam Khandaker; Desalegn Markos Shifti; Craig F Munns; Mahmudul Hassan Al Imam; Diane Maresco-Pennisi; Renarta Whitcombe (BMJ Open)
Objective To examine the overall incidence rate and trends in emergency department (ED) presentations related to asthma and allergic diseases in regional Australia with a particular focus on First Nations Australians.Design A retrospective analysis of data from the Emergency Department Information System.Setting This study used data from 12 public hospitals in Central Queensland, Australia, a region encompassing regional, rural and remote outback areas.Participants A total of 813 112 ED presentations between 2018 and 2023.Outcome measure Asthma and allergic diseases were identified using the International Classification of Diseases-Tenth Revision-Australian Modification codes.Results There were 13 273 asthma and allergic disease-related ED presentations, with an overall prevalence of 1.6% (95% CI 1.6, 1.7). There was a significantly higher incidence rate of asthma and allergic disease-related ED presentations among First Nations Australians at 177.5 per 10 000 person-years (95% CI 169.3, 186.0) compared with 98.9 per 10 000 person-years (95% CI 97.2, 100.8) among Australians of other descents. The incidence rates, with corresponding 95% CIs, of the four most common cases among First Nations Australians and Australians of other descents, respectively, were as follows: asthma (87.8 (82.0, 93.8) and 40.2 (39.0, 41.3)), unspecified allergy (55.3 (50.8, 60.2) and 36.0 (34.9, 37.1)), atopic/allergic contact dermatitis (17.1 (14.6, 19.9) and 10.6 (10.0, 11.2)) and anaphylaxis (7.2 (5.6, 9.1) and 6.2 (5.7, 6.6)).Conclusion Our findings highlight a significantly higher rate of asthma and allergic disease-related ED presentations among First Nations Australians compared with Australians of other descents. This underscores the urgent need for targeted healthcare interventions integrating culturally appropriate approaches, alongside additional research to understand causality.